Pendampingan Implementasi Kurikulum Merdeka Melalui Pelatihan Komite Pembelajaran Sekolah Penggerak - Yahrif, Muhammad; R. Supardi (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The implementation of the independent curriculum in the third year of implementation is one of the government's efforts to accelerate the process of improving and transforming education in Indonesia for the better. In its application, of course, it needs to be understood by all learning committees as the main actors implementing the independent curriculum. This community service article describes the results of the implementation of the Learning Committee Training (PKP) for the Implementation of the Independent Curriculum (IKM) in the Learning Committee in two driving schools in Soppeng Regency. The implementation of this PKP goes through four stages, namely: 1) provision of IKM material through real action training, 2) assistance in designing learning, 3) implementation of projects to strengthen the profile of Pancasila students that have been prepared, and 4) feedback or reflection on activities.The results of feedback and monitoring of PKM activities showed that 85% of participants answered very seven related to the presentation of material and discussion was enough to make the understanding of the trainees, 95% of the trainees answered very seventh for their understanding greatly improved after participating in this training activity, and 100% of the trainees answered very seventh on the material presented according to their needs.